COST ANALYSIS OF HYBRID MODEL OF SOLAR-WIND-BIOGAS PLANT (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2015)
In this paper, the power delivered by the combined system component is compared with each other and various conclusions are drawn. The various advantages and disadvantages of the system are compared, and a cost analysis of the system is carried on with the present system. The power delivered by hybrid model of PV/WIND/biogas is much higher than the PV/WIND. The system is more reliable, environmental friendly and the waste products of this sys tem do not contain any harmful gases and acids. This model uses all the renewable energy sources for electric generations which are the need of the time. With the use of energy from wind, solar, biogas plant it will help to reduce our dependency on fossil fuels. Thus, as future development of the present work, it could be very useful to set up flexible tool to model and to simplify the task of evaluating design solutions for stand-alone and distributed generations applications. We have proposed a model of 3KW that contains 1 KW of biogas plant, 1 KW of solar plant and 1 KW of wind plant. We have prepared a cost analysis report that indicates it is profitable to go for such model as it satisfies our current and future energy demands. Moreover the electricity generated by the proposed model is available at a very lesser rate as compared to our current electricity tariff rates.